Prediction markets in theory and practice - Justin Wolfers; Eric Zitzewitz (Institute for the Study of Labor (IZA), 2006)
Prediction Markets, sometimes referred to as information markets, idea futures or event futures, are markets where participants trade contracts whose payoffs are tied to a future event, thereby yielding prices that can be interpreted as market-aggregated forecasts. This article summarizes the recent literature on prediction markets, highlighting both theoretical contributions that emphasize the possibility that these markets efficiently aggregate disperse information, and the lessons from empirical applications which show that market-generated forecasts typically outperform most moderately sophisticated benchmarks. Along the way, we highlight areas ripe for future research.
Keywords: C53; D8; G14; 330; prediction markets; information markets; information aggregation; Prognose; Spekulation; Termingeschäft; USA